Dyeing of cotton and silk fabric with Tradescantia spathacea Sw. leaf aqueous extract - Kannathasan, K.; Kalaiselvi, T.; Vellaiammal, V. (Current Botany, 2024)
Colour is one of the appealing factors that impress people across the world. In every living organism in this globe i.e., insect, bird, animal, plant and human etc., colour seems to be the most attractive factor throughout the life. The Tradescantia spathacea leaf extract was used for dyeing of cotton and silk fabric. The mordants used in this study were Copper Sulphate and Myrobalan. There were three methods of mordanting carried out in this study namely, simultaneous mordanting, pre-mordanting and post mordanting. In the dyed cotton fabric, pre-mordanting treatment with myrobalan (Grey Scale Rate 4) and Copper Sulphate (Grey Scale Rate 3) showed better grey scale rating than other treatments. The silk fabrics dyed with the leaf extract resulted in grey scale rating of 3-4 or 4 for wash fastness tests. This indicates that all the natural dye applied silk fabrics showed better response than cotton in retaining the dye after washing. In staining tests (the spilling of dye/colour from the natural dyed fabrics on other cotton and wool fabrics) almost all the treatments showed very good results. The grey scale rating of 4-5 was achieved for all the dyed fabrics. Since the fabric showed better results it can be further elaborated for large scale dyeing experiments and more fastness studies like fastness to light, ironing etc. for suitable application in textile dyeing of silk fabrics.